Shared additive genetic influences on DSM-IV criteria for alcohol dependence in subjects of European ancestry - Palmer, Rohan H. C.; McGeary, John E.; Heath, Andrew C.; Keller, Matthew C.; Brick, Leslie A.; Knopik, Valerie S. (Addiction (Abingdon, England), 2015)
Background and Aims Genetic studies of alcohol dependence (AD) have identified several candidate loci and genes, but most observed effects are small and difficult to reproduce. A plausible explanation for inconsistent findings may be a violation of the assumption that genetic factors contributing to each of the seven DSM‐IV criteria point to a single underlying dimension of risk. Given that recent twin studies suggest that the genetic architecture of AD is complex and probably involves multiple discrete genetic factors, the current study employed common single nucleotide polymorphisms in two multivariate genetic models to examine the assumption that the genetic risk underlying DSM‐IV AD is unitary. Design, Setting, Participants, Measurements AD symptoms and genome‐wide single nucleotide polymorphism (SNP) data from 2596 individuals of European descent from the Study of Addiction: Genetics and Environment were analyzed using genomic‐relatedness‐matrix restricted maximum likelihood. DSM‐IV AD symptom covariance was described using two multivariate genetic factor models. Findings Common SNPs explained 30% (standard error = 0.136, P = 0.012) of the variance in AD diagnosis. Additive genetic effects varied across AD symptoms. The common pathway model approach suggested that symptoms could be described by a single latent variable that had a SNP heritability of 31% (0.130, P = 0.008). Similarly, the exploratory genetic factor model approach suggested that the genetic variance/covariance across symptoms could be represented by a single genetic factor that accounted for at least 60% of the genetic variance in any one symptom. Conclusion Additive genetic effects on DSM‐IV alcohol dependence criteria overlap. The assumption of common genetic effects across alcohol dependence symptoms appears to be a valid assumption.